2022
DOI: 10.3389/fpsyg.2022.784471
|View full text |Cite
|
Sign up to set email alerts
|

Self-Report Measures of Procrastination Exhibit Inconsistent Concurrent Validity, Predictive Validity, and Psychometric Properties

Abstract: Procrastination is a chronic and widespread problem; however, emerging work raises questions regarding the strength of the relationship between self-reported procrastination and behavioral measures of task engagement. This study assessed the internal reliability, concurrent validity, predictive validity, and psychometric properties of 10 self-report procrastination assessments using responses collected from 242 students. Participants’ scores on each self-report instrument were compared to each other using corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…This is precisely because they want to quickly eliminate what they do not like. In other studies there were some students who engaged in an early action pacing style (“precrastination”), some students who engaged in a steady work pacing style (“steady work”), and some students who exhibited a deadline action pacing style (“procrastination”) (Vangsness et al, 2022; Vangsness & Young, 2020). These studies reverse the traditional finding that ways to do a task efficiently were mostly equated with minimizing costs.…”
Section: Diversification Of Procrastinationmentioning
confidence: 99%
“…This is precisely because they want to quickly eliminate what they do not like. In other studies there were some students who engaged in an early action pacing style (“precrastination”), some students who engaged in a steady work pacing style (“steady work”), and some students who exhibited a deadline action pacing style (“procrastination”) (Vangsness et al, 2022; Vangsness & Young, 2020). These studies reverse the traditional finding that ways to do a task efficiently were mostly equated with minimizing costs.…”
Section: Diversification Of Procrastinationmentioning
confidence: 99%
“…In this regard, the various available scales may differ primarily in their theoretical foundations, the specific assessment context for which they were designed, or their technical characteristics. Vangsness et al (2022) assessed the psychometric properties of 10 procrastination measures and found that certain scales, e.g., irrational procrastination scale (IPS; Steel, 2010), pure procrastination scale (PPS; Steel, 2010), or Tuckman procrastination scale (TPS; Tuckman, 1991), displayed better psychometric properties than others, e.g., active procrastination scale (APS; Choi and Moran, 2009), adult inventory of procrastination (AIP; McCown and Johnson, 1989).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…While this study focused on employed adults, it's essential to explore procrastination habits, both traditional and other variants, particularly among university students (Vangsness et al, 2022;Vangsness & Young, 2020). For example, some students consistently produce reports at a steady pace, others procrastinate until just before the deadline (procrastination), and still others complete and submit their reports at an early stage (precrastination).…”
Section: Limitation and Future Researchmentioning
confidence: 99%